2020
DOI: 10.1038/s41467-020-14752-9
|View full text |Cite
|
Sign up to set email alerts
|

Chiral twisting in a bacterial cytoskeletal polymer affects filament size and orientation

Abstract: In many rod-shaped bacteria, the actin homolog MreB directs cell-wall insertion and maintains cell shape, but it remains unclear how structural changes to MreB affect its organization in vivo. Here, we perform molecular dynamics simulations for Caulobacter crescentus MreB to extract mechanical parameters for inputs into a coarse-grained biophysical polymer model that successfully predicts MreB filament properties in vivo. Our analyses indicate that MreB double protofilaments can exhibit left-handed twisting th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 59 publications
(80 reference statements)
2
23
0
Order By: Relevance
“…Molecular dynamics simulations have shown that the twist of MreB double protofilaments can be reduced by membrane binding. The moderated dynamics of MreB filaments resulted in shorter filaments, and possibly provides tuning to their flexibilty and length 44 . The untwisted antiparallel structure of pairs of protofilaments can allow bending of the MreB filaments, which may stabilize the curvature of a membrane 44 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular dynamics simulations have shown that the twist of MreB double protofilaments can be reduced by membrane binding. The moderated dynamics of MreB filaments resulted in shorter filaments, and possibly provides tuning to their flexibilty and length 44 . The untwisted antiparallel structure of pairs of protofilaments can allow bending of the MreB filaments, which may stabilize the curvature of a membrane 44 .…”
Section: Discussionmentioning
confidence: 99%
“…The moderated dynamics of MreB filaments resulted in shorter filaments, and possibly provides tuning to their flexibilty and length 44 . The untwisted antiparallel structure of pairs of protofilaments can allow bending of the MreB filaments, which may stabilize the curvature of a membrane 44 . High calcium concentrations 45 , near a membrane, may induce longer persistence lengths in MreB polymers.…”
Section: Discussionmentioning
confidence: 99%
“…In the rod-shaped bacterium Escherichia coli, left-handed chirality of the MreB cytoskeleton (a bacterial F-actin-like polymer) guides local insertion of wall material into the peptidoglycan network, and causes cells to twist in a left-handed helix during elongation growth [69]. Molecular dynamics simulations for MreB in Caulobacter crescentus, another rod-shaped bacterium, suggest MreB double protofilaments can exhibit left-handed twisting and induce a stable membrane curvature when bound to the membrane [70]. Chiral arrangements of polar cytoskeletons underneath the cell-enclosing membrane may provide a common paradigm for helical growth in cylindrical plant cells and rod-shaped bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, as in most rod-shaped bacteria, M. xanthus MreB plays conserved roles in PG assembly. As MreB filaments are intrinsically curved, and bind to the cytoplasmic membranes, the balance between filament bending and membrane deformation can lead MreB filaments to localize at inwardly curved regions [ 31 , 74 , 75 , 76 , 77 , 78 ]. This localization preference, in turn, affects the localization and dynamics of Rod complexes, which could be sufficient for the maintenance of rod shape [ 31 , 32 , 33 , 71 , 76 , 79 , 80 ].…”
Section: Perspectivesmentioning
confidence: 99%